2011
DOI: 10.3415/vcot-10-01-0013
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical discrepancy between cage size and efficient tibial tuberosity advancement in dogs treated for cranial cruciate ligament rupture

Abstract: A discrepancy does exist between the desired tibial tuberosity advancement and the actual advancement in a direction parallel to the TPA, when the tibial tuberosity is not translated proximally. Although this has an influence on the final PTA, further studies are warranted to evaluate whether this is clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
0
8
1
1
Order By: Relevance
“…However, it is has been shown that there is a theoretical discrepancy between the cage size and the resultant tibial tuberosity advancement, with the cage size consistently providing less tibial tuberosity advancement than predicted [ 12 ]. This occurs as the advancement distance required is measured in a direction parallel to the tibial plateau, whereas the plane of the tibial crest osteotomy is not perpendicular to the tibial plateau.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is has been shown that there is a theoretical discrepancy between the cage size and the resultant tibial tuberosity advancement, with the cage size consistently providing less tibial tuberosity advancement than predicted [ 12 ]. This occurs as the advancement distance required is measured in a direction parallel to the tibial plateau, whereas the plane of the tibial crest osteotomy is not perpendicular to the tibial plateau.…”
Section: Introductionmentioning
confidence: 99%
“…A recent trigonometric study has shown that there is a discrepancy between preoperative PLA measurements and the actual PLA achieved by advancing the tibial tuberosity as calculated [20]. The findings of this study have since been substantiated clinically with actual tibial tuberosity advancement achieved during the MMP being 30% lower than the calculated wedge size used [14].…”
Section: Introductionmentioning
confidence: 68%
“…One study based on a MMP type procedure found that with larger cage sizes and steeper tibial plateau slopes, a larger discrepancy between preoperative measurements and postoperative outcome can be expected [20]. This seems to occur because the direction of the preoperative measurements along the axis of the tibial plateau or common tangent differs to the direction of advancement achieved clinically when the tibial tuberosity is rotated around its distal attachment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rzeczywisty przebieg plateau kości piszczelowej ma ogromne znacznie podczas określania kąta inklinacji więzadła prostego rzepki (patellar tendon angle -PTA), wykorzystywanego w procedurze wysunięcia guzowatości kości piszczelowej (TTA -tibial tuberosity advancement) oraz jej modyfikacjach (TTA Rapid) (7,12,15,17,37), a wartość TPA wyższa niż 30° sprawia, że metoda nie jest odpowiednio skuteczna (8,20).…”
Section: Zastosowanie Pomiaruunclassified